Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.fluid.2014.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Phase equilibria of the water+1-butanol+toluene ternary system at 101.3kPa

Abstract: Please cite this article as: Vicente Gomis, Alicia Font, María Dolores Saquete, Jorge García-Cano, Phase equilibria of the water + 1-butanol + toluene ternary system at 101.3kPa, Fluid Phase Equilibria http://dx.doi.org/10.1016/j.fluid. 2014.10.038 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The Fischer Minitron VLE was used in the range 10-1026 mbar and the Mensor High-Speed Pneumatic Pressure Controller model CPC3000 above that range. The apparatus is a wellknown phase equilibria determination equipment validated many times by our research group [13][14][15][16][17][18][19][20]. Moreover, prior to the determination of new experimental data, the overall performance is checked with known data (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The Fischer Minitron VLE was used in the range 10-1026 mbar and the Mensor High-Speed Pneumatic Pressure Controller model CPC3000 above that range. The apparatus is a wellknown phase equilibria determination equipment validated many times by our research group [13][14][15][16][17][18][19][20]. Moreover, prior to the determination of new experimental data, the overall performance is checked with known data (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…NRTL [1] and similar equations for the liquid phase excess Gibbs free energy has shown severe limitations to simultaneously represent VLE and VLLE data [2][3][4][5]. Additionally, the correlation provided by these types of equations for ternary systems, as shown in the Data collection of DECHEMA Data Series [6] may be acceptable when dealing only with the ternary data but yield poorer results when attempting the simultaneous correlation of the ternary and the binary data.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Based on the mean deviations of water and 1-butanol in the organic and aqueous phases, NRTL was marginally better than UNIQUAC for the organic phase prediction, but considerably worse for the aqueous phase prediction. In another study by the same group, 35 the VLLE of the water− 1-butanol−toluene system was determined. Model predictions using NRTL and UNIQUAC found that UNIQUAC consistently had lower mean deviations for the prediction of water and 1-butanol in the organic and aqueous phases.…”
Section: Suitability Of Models Formentioning
confidence: 99%